Nonfreezing Cold-Induced Injuries. Issue 1 (1st March 2011) - Imray, Chris; Richards, P; Greeves, J; Castellani, JW
Abstract : Non-freezing cold injury (NFCI) is the Cinderella of thermal injuries and is a clinical syndrome that occurs when tissues are exposed to cold temperatures close to freezing point for sustained periods. NFCI is insidious in onset, often difficult to recognize and problematic to treat, and yet the condition accounts for significant morbidity in both military and civilians who work in cold conditions. Consequently recognition of those at risk, limiting their exposure and the appropriate and timely use of suitable protective equipment are essential steps in trying to reduce the impact of the condition. This review addresses the issues surrounding NFCI.